A comprehensive review of finerenone—a third-generation non-steroidal mineralocorticoid receptor antagonist - Zhai, Shuhui; Ma, Baisheng; Chen, Weiwei; Zhao, Qini (Frontiers in Cardiovascular Medicine, 2024)
Multiple studies have shown that finerenone (BAY 94-8862), a third-generation non-steroidal mineralocorticoid receptor antagonist (MRA), possesses different or superior mechanisms of action to traditional MRAs. Specifically, animal and cell-based experiments have demonstrated that this compound exerts multiple effects including fibrosis inhibition, reduced pulmonary artery pressure, improved diabetic retinopathy, enhanced endothelial functions, metabolic optimization as well as reduced oxidative stress, thereby exerting overall positive effects on renal and cardiovascular diseases. Consequently, clinical research, such as the FIGARO-DKD and FIDELIO-DKD trials, has demonstrated dual benefits for patients with type 2 diabetes mellitus and chronic kidney disease (T2DM-CKD), especially by validating MRAs' potential in reducing risks of renal and cardiovascular composite endpoints. Currently, cardiovascular indications for finerenone are limited to patients with T2DM-CKD, while its use in non-T2DM CKD patients remains at clinical trial stages. Despite showing good safety and efficacy in T2DM-CKD patients, there are insufficient corresponding data for those presenting chronic kidney disease without diabetes (ndCKD). Furthermore, the application of this compound in diseases such as primary aldosteronism and its association with cancer risk need to be further validated through larger-scale and longer-term clinical studies. Nevertheless, the development of finerenone provides an additional option for treating cardiovascular and renal diseases. With further research, it is expected that finerenone will be relevant to a broader range of CKD patient populations by addressing current knowledge gaps to comprehensively evaluate its clinical value and potentially alter existing treatment strategies. The current review aims to comprehensively analyze the basic research and clinical advancements involving finerenone in order to explore its prospects for treating cardiovascular and renal diseases, while addressing unmet needs in current treatment strategies. Additionally, through a comprehensive analysis of relevant research findings, a deeper understanding of finerenone's drug characteristics will be provided alongside scientific guidance for future treatment strategies and their clinical significance.